Research Progress in Mitochondrial Treatment and Mechanism in Occurrence of Lung Cancer - Fasheng, Wu; Hui, Zhang; Jiatong, Xie; Jianfu, Li; Hui, Chen; Shijin, Lu (Zhongliu fangzhi yanjiu, 2024)
Lung cancer is characterized by high incidence and mortality rates and invasiveness, and its occurrence and development are influenced by various factors. Mitochondria, as ubiquitous organelles in the human body, regulate cellular processes, such as metabolism, signal transduction, oxidative stress, and genomic instability, thereby affecting the initiation and progression of lung cancer. This article summarizes the recent research progress on mitochondrial-targeted drugs, mitochondrial transfer, and mitochondrial gene therapy for lung cancer treatment. This work also discusses the principles and prospects of mitochondrial therapy to provide new insights for lung cancer treatment.